CACS-FUNDEB : território de subjetividade e de possibilidades de práticas democráticas - Batista, José Ricardo (2017)
In this work the object is the discourses articulated by members of the CACS-FUNDEB (Council for Social Monitoring and Control) of cities in the interior of the State of São Paulo during the years 2015 and 2016. The aim of this research was to analyze the discursive relationship within CACS-FUNDEB in order to understand the process of subjectivation, the counselor's perception of himself and how practices are articulated with knowledge and power in the constitution of subjects. In bringing CACS-FUNDEB to the center of this research, it was based on the idea that finance is a dimension of democratic management, but that it could not be limited to surveillance and monitoring the application of resources because of the ideal surrounding creation from education fund. The study points in the direction that the collegiate is inserted in the conception of democratic management as important space of social participation, but that still needs to conquer its autonomy and effectiveness. In the relation the subject produces knowledge and powers that can affirm the scheme of domination, legitimizing such practice, but also can resist. The theoreticalmethodological procedure is based on bibliographical research and discussion of the speeches permeated by the French Discourse Analysis, with a theoretical foundation in Michel Foucault that brings a study about the parresía allowing to understand the importance of truth as a form of resistance. Against this backdrop, the CACS-FUNDEB is inserted as a space for practicability, exercising the freedom to speak the truth as a form of resistance, as an instrument of institutional and financial decentralization, attributing to society and the state a posture from a responsible management perspective. There is an intimate relationship with the notion of the care of the public welfare because the individual is part of this "common" that demands a change of individual behavior, to live righteously, to speak frankly and to act according to this discourse.